2015
DOI: 10.1002/marc.201500429
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of Poly(butyl methacrylate) by Molecular Topology Using Multidetector Thermal Field‐Flow Fractionation

Abstract: Thermal field-flow fractionation (ThFFF) is an interesting alternative to column-based fractionation being able to address different molecular parameters including size and composition. Until today it has not been shown to be able to fractionate polymers of similar molar masses and chemical compositions by molecular topology. The present study demonstrates that poly(butyl methacrylates) with identical molar masses can be fractionated by ThFFF according to the topology of the butyl group. The influence of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 21 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Previous studies on microstructure-based separations by ThFFF showed that a theta solvent can be a promising solvent to significantly influence retention behavior because polymer–solvent interactions are significantly different for a theta solvent at various temperatures (especially at the theta temperature) than for a thermodynamically good solvent. ,, Thus, CH was selected for this study as it is a theta solvent for PS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on microstructure-based separations by ThFFF showed that a theta solvent can be a promising solvent to significantly influence retention behavior because polymer–solvent interactions are significantly different for a theta solvent at various temperatures (especially at the theta temperature) than for a thermodynamically good solvent. ,, Thus, CH was selected for this study as it is a theta solvent for PS.…”
Section: Resultsmentioning
confidence: 99%
“…Thermal field-flow fractionation (ThFFF) is a subtechnique of the field-flow fractionation family that employs a temperature gradient perpendicular to a carrier liquid flowing through an open, ribbon-like channel in order to fractionate analytes according to size, chemical composition and microstructure. The applied temperature gradient drives analytes from the hot wall toward the cold wall (accumulation wall) of the channel. This temperature-induced migration is termed thermal diffusion and is described by the thermal diffusion coefficient, D T, which (among other factors) is dependent on the chemical nature of the analytes and the solvent. ,,, Thermal diffusion is balanced by normal diffusion which is the migration of analytes away from the accumulation wall toward the center of the channel due to increasing analyte concentration. , Normal diffusion is described by the normal diffusion coefficient, D , and is dependent on the size of the analytes in solution. ,, …”
Section: Introductionmentioning
confidence: 99%
“…ThFFF is a sub‐technique of FFF that applies a temperature drop across an open, ribbon‐like channel in order to fractionate analytes according to size, chemical composition and microstructure . The first reported attempts to fully utilise the advantages and unique separation capabilities of ThFFF to separate micelles according to corona composition were performed on poly(methyl methacrylate)–polystyrene micelles in acetonitrile using a multidetector ThFFF setup as illustrated in Scheme .…”
Section: Characterisation Of Micelle Property Distributionsmentioning
confidence: 99%